2021
DOI: 10.1371/journal.pntd.0009994
|View full text |Cite
|
Sign up to set email alerts
|

An aromatic imidazoline derived from chloroquinoline triggers cell cycle arrest and inhibits with high selectivity the Trypanosoma cruzi mammalian host-cells infection

Abstract: Trypanosoma cruzi is a hemoflagellated parasite causing Chagas disease, which affects 6–8 million people in the Americas. More than one hundred years after the description of this disease, the available drugs for treating the T. cruzi infection remain largely unsatisfactory. Chloroquinoline and arylamidine moieties are separately found in various compounds reported for their anti-trypanosoma activities. In this work we evaluate the anti-T. cruzi activity of a collection of 26 “chimeric” molecules combining cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Subsequent analysis revealed that no changes in mitochondrial function were detected during short-term incubations. However, after prolonged incubation times, 51 was able to decrease intracellular Ca 2+ , ATP levels, and collapse mitochondrial inner membrane potential (Cuevas- Hernández et al, 2021).…”
Section: Other Heterocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent analysis revealed that no changes in mitochondrial function were detected during short-term incubations. However, after prolonged incubation times, 51 was able to decrease intracellular Ca 2+ , ATP levels, and collapse mitochondrial inner membrane potential (Cuevas- Hernández et al, 2021).…”
Section: Other Heterocyclic Compoundsmentioning
confidence: 99%
“…Subsequent analysis revealed that no changes in mitochondrial function were detected during short‐term incubations. However, after prolonged incubation times, 51 was able to decrease intracellular Ca 2+ , ATP levels, and collapse mitochondrial inner membrane potential (Cuevas‐Hernández et al., 2021). Two series of diaryl‐tetrahydrofuran and ‐furan were prepared and tested for anti‐anti‐trypanosomal action against T. cruzi , in trypomastigote and amastigote forms.…”
Section: Synthetic Antichagas Agentsmentioning
confidence: 99%
“…Further attempts to develop improved trypanocidal agents have included studies on benzazoles and their amidine derivatives, where enhancement of activity has been achieved through optimization of physicochemical parameters and ADME properties. The introduction of nitrogen atoms into the aromatic rings can change the lipophilicity and polarity of the resulting aza analogues, enabling them to cross the BBB. , Some benzimidazole and benzothiazole derivatives have been shown to have potent anti-trypanosomatid activity.…”
Section: Introductionmentioning
confidence: 99%